2012
DOI: 10.3766/jaaa.23.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Missing Links in Some Curious Auditory Phenomena: A Tale from the Middle Ear

Abstract: The significant effects of age, gender, ear, and frequency on BMEPR parallel ear- and gender-related differences in hearing sensitivity, ear, and gender differences in the prevalence of spontaneous otoacoustic emissions (OAEs), gender differences in the magnitude of transient evoked OAEs, and ear differences in transient evoked contralateral OAE suppression effects reported in the literature. While original discussions of these aforementioned effects focused primarily on endocochlear and olivocochlear mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The gender effect demonstrated in the present study is consistent with Feeney and Sanford (2004) who reported significant gender differences with females having lower EA (higher ER) than males at 794 and 1000 Hz, but higher EA (lower ER) at 5040 Hz. Carpenter et al (2012) also found significant gender related differences in EA from 1007 to 1265 Hz and from 3000 to 5039 Hz. Shahnaz and Bork (2006) suggested that difference in EA between males and females may be attributed to differences in both middle ear and ear canal volume due to difference in body size between the two genders.…”
Section: Caucasians Wideband Energy Absorbance In Adultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The gender effect demonstrated in the present study is consistent with Feeney and Sanford (2004) who reported significant gender differences with females having lower EA (higher ER) than males at 794 and 1000 Hz, but higher EA (lower ER) at 5040 Hz. Carpenter et al (2012) also found significant gender related differences in EA from 1007 to 1265 Hz and from 3000 to 5039 Hz. Shahnaz and Bork (2006) suggested that difference in EA between males and females may be attributed to differences in both middle ear and ear canal volume due to difference in body size between the two genders.…”
Section: Caucasians Wideband Energy Absorbance In Adultsmentioning
confidence: 67%
“…Although Rosowski et al (2012) reported that ER measured from females were generally higher than males at frequencies ≤2000 Hz and lower from 3000 to 6000 Hz, only ER at 4000 Hz was found to be statistically significant with gender. Besides the two aforementioned studies, gender differences have also been reported by Carpenter et al (2012 Table 1.…”
Section: Introductionmentioning
confidence: 89%
“…The wideband tympanometry technique is more sensitive and specific than standard clinical testing to many conductive disorders including OME, since it measures the full range of frequencies important for speech perception (Hunter, Prieve, Kei, & Sanford, 2013). This technique has also been used to interpret high frequency hearing thresholds (Margolis et al, 2000) and cochlear measures with respect to possible middle ear effects (Carpenter, Cacace, & Mahoney, 2012).…”
Section: Audiological Assessmentsmentioning
confidence: 99%
“…Moreover, there are assertions that malfunctions of the middle ear affects inner ear functioning. For instance, middle ear measurements by broadband middle ear power reflectance (BMEPR) suggested middle ear transmission characteristics played a role in active physiologic process within the inner ear, measured by spontaneous otoacoustic emissions (SPOAEs) 11 . Similarly, Uchida et al confirmed that the condition of the middle ear function measured by tympanometry affects the functioning of the cochlear measured by distortion-product otoacoustic emissions (DPOAEs) 12 It is thus important that middle ear dynamics and functioning be assessed in order to effectively manage other forms of hearing impairment in elderly subjects.…”
Section: Discussionmentioning
confidence: 99%